STEPWISE SELECTIVE LEACHING OF THE MARINE FERROMANGANESE FORMATIONS FOR DETERMINING THEIR PHASE COMPOSITION: EXPERIENCE OF THE TECHNIQUE APPLICATION IN THE CENTER FOR COLLECTIVE USE OF FEGI FEB RAS - M. G. Blokhin; N. V. Zarubina; Yu. M. Ivanova; P. E. Mikhailik; V. V. Ivanov (Геодинамика и тектонофизика)
This paper considers chemical and analytical aspects of the preparation of samples of marine ferromanganese deposits (FMD) by stepwise selective leaching to determine their phase composition. The behaviour of samples with different mineral and chemical compositions at various stages of their preparation was studied on the base of the FMD sample from the Eastern Pacific. The paper shows the necessity of further scanning-electron-microscopy (SEM) method-based research to control the complete dissolution of Fe compounds responsible for accumulating trace elements, which are geochemical indicators.